Strategi Manajemen Keuangan Internasional Dalam Meningkatkan Daya Saing Perusahaan Global - Suci Maharani Pane; Hendra Ibrahim (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
With the opportunity to compete in an open global market, and the existing potential that has not been utilized properly, the competitiveness of global companies becomes very tight. Competition is natural, because competition creates the color and impression of competition in business competitions. With competition, we can also find out how far we can survive in the path we are on. With competitiveness we can also find out things for evaluation. However, we will pin this victory in terms of financial management. Therefore, the aim of this research is to find out how international financial management strategies can increase the competitiveness of global companies. This research uses a qualitative methodology by obtaining data from literature studies using secondary data, which is completed by completing a literature review and concluding the article. The result is that the strategy that can be used and applied in this case during competition is determining the composition of capital because after planning and forecasting are made, the capital structure can be decided, followed by a mixture of debt and equity which is used to finance future profitable investment opportunities, so with this the company Don't be afraid and don't lose in the competition because you already have provisions for the future now